Knowledge and Power in Islamic Historiography: A Dialectical Reading through the Lens of Michel Foucault - Soetomo, Greg (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2024)
This article examines the development of Islamic historiography through the framework of epistemic archaeology, drawing on Michel Foucault’s theories of discourse, power, and knowledge. Employing a critical-historical and genealogical methodology, the study integrates close textual analysis of classical Islamic sources—such as hadith, sīrah, maghāzī, and asmā’ al-rijāl—with discourse analysis to trace how historical narratives were shaped by theological, legal, and political interests. It examines the complex role of early transmitters, particularly the ṣaḥābah, in constructing the foundations of historical authority, and highlights how definitions of authenticity and legitimacy evolved amid sectarian and epistemological contestations. The research explores the transition from oral transmission to systematic historiographical writing in Arabic, followed by the Persianization of Islamic historical narratives under the Ghaznavid dynasty. Rather than treating Islamic historiography as a linear or unified tradition, this study argues that it constitutes a dynamic and heterogeneous field marked by multiple epistemic ruptures and reconfigurations. By situating these shifts within a Foucauldian analytic, the article shows how Islamic historical writing functioned not only as a record of the past but also as a mechanism for producing truth, governing memory, and regulating religious authority within diverse Islamic communities.